DEVELOPMENT OF WATER QUALITY MONITORING SYSTEM IN SHRIMP PONDS BASED ON INTERNET OF THINGS (IOT) - Musdalifah, Musdalifah; Ruslan, Ruslan; Zulhajji, Zulhajji (Journal of Electrical Engineering and Informatics, 2024)
This type of research is research and development (R&D) which uses the waterfall development model. The aim of this research is to produce a water quality monitoring system in shrimp ponds based on the Internet of Things (IoT) and to find out the results of testing the development of the system using the ISO 25010 standard. This development involves the application of ESP32, Relay, Toa Siren, DS18b20 Temperature Sensor, pH Sensor Module 4502C, Water Salinity and Turbidity Sensor which allows users to get real-time pond water quality monitoring information via the Telegram application. The test results for the reliability aspect have met the fault tolerance sub-characteristic standards because the percentage of measurement error obtained for the temperature sensor was 0.10%, pH 0.54%, salinity 1.19%, and turbidity 1.00%, still within the permitted tolerance limits. Functionality suitability testing shows that this tool obtains a percentage of 100%, indicating that the system is suitable for use. This tool also meets the portability aspect because it can be used on various devices with different operating systems. Apart from that, the usability evaluation results from user responses are in the very good category with an average of >4.2.